AN ANALYSIS OF ELEVENTH-GRADE STUDENTS' ABILITY TO WRITE SHORT STORIES BASED ON PERSONAL EXPERIENCE - Thresia Trivict Semiun; Delicia Abani (MEDIA DIDAKTIKA, 2025)
This study examined eleventh-grade students' ability to write short stories based on personal experience at SMAN 2 Kefamenanu. The main focus of this research was to analyze five aspects of writing short stories, namely content, organization, grammar, mechanics, and vocabulary, as well as the level of ability and difficulty of the students in writing short stories. It applied a qualitative and quantitative approach with tests and interviews as the instrument. The results showed that students had a "good" level of writing ability, with an average score of 81.31. However, some students still encountered difficulties in several aspects of writing, namely grammar, vocabulary, mechanics, and content. These difficulties occurred because students could not combine good sentences, lacked vocabulary, could not place punctuation marks and capital letters correctly, and could not explain the meaning of the topic they had determined. Therefore, errors occurred in their writing. The study provided advice for teachers to improve their teaching methods.